ISOLTRAP pins down masses of exotic nuclides - Blaum, Klaus; Herfurth, Frank; Kluge, Heinz-Jürgen (Journal of physics. G, Nuclear and particle physics, 2005)
The mass of radionuclides contribute to a variety of fundamental studies including tests of the weak interaction and the standard model. The limits of mass measurements on exotic nuclides have been extended considerably by the Penning-trap mass spectrometer ISOLTRAP at the ISOLDE facility at CERN. Recent ISOLTRAP measurements are summarized and current technical improvements are outlined.
Gesehen am 03.03.2020